DataCite – Contributing to the PID infrastructure in Africa - Obileye, Bosun; Havemann, Jo; Ezeike, Ebuka (My University, 2023)
This session is part of the AfricArXiv Webinar Series on Open Science for the Discoverability of African Research.
The Slides are available at 10.5281/zenodo.10241917 https://africarxiv.pubpub.org/pub/cj9x4ohj#nnozkgs7knz
Keywords: DataCite; PID; infrastructure